(untitled) (Journal of Pharmaceutical Negative Results, 2018)
The study's goals were to: (1) evaluate how interprofessional education (IPE) can help nursing and occupational therapy students become more knowledgeable and proficient in respiratory therapy (RT) medical devices and techniques; (2) encourage collaborative behaviors; and (3) assess how well nursing and RT students understand safe patient transfers and how to handle a patient's medical lines during transfers.METHODS: Data from an IPE high-fidelity simulation experience involving 73 nursing, occupational therapy, and RT students at an academic medical institution was gathered using a prospective mixed methods approach. The IPE experience was developed in accordance with the Interprofessional Education Collaborative roles and responsibilities and the Interprofessional Communication sub- competency.RESULTS: 82.2% of respondents completed the pre-post paired survey. Prominent improvements in students' perceptions of learning varied by occupation. According to student assessments of the IPE experience, students were more likely to work with the other represented professions in the future and gained a better understanding of the procedures they carried out. Outcomes: IPE enhanced students' understanding of the competency domain of roles and responsibilities. Students studying occupational therapy and nursing in particular became more cognizant of the knowledge and skill set required for the RT profession.